Inherited chromosomally integrated human herpesvirus‐6 in a patient with XIAP deficiency. Issue 5 (8th June 2020) - Inoue, Kento; Miura, Hiroki; Hoshino, Akihiro; Kamiya, Takahiro; Tanita, Kay; Ohye, Tamae; Park, Myoung‐Ja; Yanagimachi, Masakatsu; Takagi, Masatoshi; Imai, Kohsuke; Morio, Tomohiro; Yoshikawa, Tetsushi; et al.
Abstract: Human herpesvirus‐6 (HHV‐6) is a common pathogen affecting the human population. Primary HHV‐6 infection generally occurs during infancy and causes exanthema subitum. Moreover, HHV‐6 may exhibit inherited chromosomally integrated HHV‐6 (iciHHV‐6) in certain individuals. Although iciHHV‐6 is generally known to be nonpathogenic, it may cause reactivation in patients with primary immunodeficiency disease (PID). XIAP deficiency is a rare PID characterized by recurrent hemophagocytic lymphohistiocytosis (HLH). It has been reported that the Epstein‐Barr virus primarily causes HLH; however, the other pathogens, including HHV‐6, can also cause this complication. We encountered a case of XIAP deficiency accompanied by iciHHV‐6. He suffered from recurrent HLH, for which allogeneic bone marrow transplantation (BMT) was performed as a curative therapy. During the course of BMT, the patient experienced HLH three times, but there was no reactivation of endogenous HHV‐6 from iciHHV‐6. Finally, the patient achieved complete donor chimerism and a decline in HHV‐6 DNA copy number in whole blood. This case report demonstrates no evidence of reactivation of iciHHV‐6 during BMT in a patient with XIAP deficiency.